Deep Learning Strategies for Visual Pattern Analysis in Metallic Surfaces - Lima, Sandro Bessa de; Duarte, Julio Cesar (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2025: Proceedings of the 31st Brazilian Symposium on Multimedia and the WebDO - 10.5753/webmedia.2025.16094, 2025)
Advances in multimedia systems and computer vision have enabled each time more sophisticated methods that are able to analyze complex visual patterns in industrial contexts. The inspection of failures in metallic alloys is important for sectors such as aerospace and defense, yet it faces limitations due to reliance on manual methods and data scarcity. This research presents a systematic approach for selecting convolutional neural network architectures by integrating data augmentation, image segmentation, and self-supervised learning. In particular, it uses the DINO technique to generate interpretable attention maps, enhancing model transparency and performance in defect detection tasks. The method was validated using three architectures, ResNetInceptionV2, DenseNet, and Xception, with DenseNet combined with DINO achieving the best results. Key contributions include the release of a hybrid dataset (real and synthetic), effective strategies for handling class imbalance, and a comparative study of architectures, offering insights for future industrial applications and deep learning research applied to pattern detection on metallic surfaces.